«Io sto bene, io sto male, io non so cosa fare». Generazione X, alternative rock e film di formazione anni Novanta (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
The paper investigates the “90s cult movies” compilation soundtracks of Enza Negroni’s “Jack Frusciante è uscito dal gruppo” (1996) and Davide Ferrario’s “Tutti giù per terra” (1997), both produced by Consorzio Produttori Indipendenti. It explores the relation between Generation X and 90s Italian films – a type of cinema that Vito Zagarrio defines «in transition» (2000), «with ambiguous forms and surfaces» (2002: 34) – through songs in the films as “Nuotando nell’aria” (Marlene Kuntz, 1994) and “A tratti” (C.S.I., 1994), which constitute the generational key and reestablish a three-dimensional realm, going beyond the image and “embodying” the characters’ “coming-of-age”.